Multi-omics analysis of miRNA-mediated intestinal microflora changes in crucian carp Carassius auratus infected with Rahnella aquatilis - Huo, Jiaxin; Li, Xiaowei; Hu, Xiucai; Lv, Aijun (Frontiers in Immunology, 2024)
Infection by an emerging bacterial pathogen Rahnella aquatilis caused enteritis and septicemia in fish. However, the molecular pathogenesis of enteritis induced by R. aquatilis infection and its interacting mechanism of the intestinal microflora associated with microRNA (miRNA) immune regulation in crucian carp Carassius auratus are still unclear. In this study, C. auratus intraperitoneally injected with R. aquatilis KCL-5 was used as an experimental animal model, and the intestinal pathological changes, microflora, and differentially expressed miRNAs (DEMs) were investigated by multi-omics analysis. The significant changes in histopathological features, apoptotic cells, and enzyme activities (e.g., lysozyme (LYS), alkaline phosphatase (AKP), alanine aminotransferase (ALT), aspartate transaminase (AST), and glutathione peroxidase (GSH-Px)) in the intestine were examined after infection. Diversity and composition analysis of the intestinal microflora clearly demonstrated four dominant bacteria: Proteobacteria, Fusobacteria, Bacteroidetes, and Firmicutes. A total of 87 DEMs were significantly screened, and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that the potential target genes were mainly involved in the regulation of lipid, glutathione, cytosine, and purine metabolism, which participated in the local immune response through the intestinal immune network for IgA production, lysosome, and Toll-like receptor (TLR) pathways. Moreover, the expression levels of 11 target genes (e.g., TLR3, MyD88, NF-κB, TGF-β, TNF-α, MHC II, IL-22, LysC, F2, F5, and C3) related to inflammation and immunity were verified by qRT-PCR detection. The correlation analysis indicated that the abundance of intestinal Firmicutes and Proteobacteria was significantly associated with the high local expression of miR-203/NF-κB, miR-129/TNF-α, and miR-205/TGF-β. These findings will help to elucidate the molecular regulation mechanism of the intestinal microflora, inflammation, and immune response-mediated miRNA–target gene axis in cyprinid fish.